Spatial and temporal distribution of Aedes albopictus monitored by mosq-ovitrap in Songjiang District of Shanghai in 2018—2020 - PANG Bowen; LIU Hongxia; LYU Xihong; LU Weiwei; GUO Xiaoqin; FEI Shengjun (Shanghai yufang yixue, 2022)
ObjectiveBased on mosq-ovitrap monitoring method of Aedes albopictus， to determine the spatial and temporal distribution of Aedes albopictus in Songjiang District and provide scientific evidence for prevention and control of mosquito-borne diseases.MethodsFrom May to October， 2018‒2020， density of Aedes albopictus was monitored by using the mosq-ovitrap method. Sub-districts and towns were used as the monitoring units and the difference in mosquito ovitrap index （MOI） was compared by seasons， years and habitats.ResultsThe total number of positive mosquito ovitraps was 1049 in 2018‒2020， and the average MOI was 8.10. Four sub-districts/towns in the urban area and the northern area had the relatively high MOIs. Moreover， MOIs in residential and external environments were higher than other habitats. In addition， MOI of Aedes albopictus decreased over years from 2018 to 2020.ConclusionAedes albopictus is widely distributed in Songjiang District. Although the number of mosquito decreased over years after the implementation of mosquito control measures， reproduction of mosquito remains excessive in some areas and seasons. It is necessary to perform targeted control measures based on comprehensive monitoring methods.